Closure of Large Patent Ductus Arteriosus in a Patient with Severe Pulmonary Hypertention by Amplatzer Septal Occluder (ASO) - A Case Report - Fatema, Nurun Nahar (Journal of Armed Forces Medical College, Bangladesh, 2009)
A large patent ductus arteriosus (PDA) of 15 mm size with severe pulmonary hypertension was detected in an eighteen year old male. He was planned for device closure. After checking reversibility of pulmonary vascular bed, a 16 mm x 14 mm PDA device was deployed without releasing from delivery cable and haemodynamic response of patient was observed for one hour. As there was no hypertensive crisis, implantation of a device was planned. 16 mm device appeared small as there was some leakage of dye. So PDA device was taken out, an 18 mm Amplatzer septal occluder was then used for complete occlusion of huge PDA. Patient was discharged from hospital next morning. Echocardiography before discharge showed no residual shunt, left pulmonary artery stenosis or coarctation of aorta. Key Words: Closure of patent ductus arteriosus (PDA closure), Amplatzer septal occluder (ASO). doi: 10.3329/jafmc.v5i1.2852 JAFMC Bangladesh. Vol 5, No 1 (June) 2009 pp.46-48